Acute‑on‑chronic slipped femoral epiphysis following posterior spinal fusion due to idiopathic scoliosis: Case report. Issue 3 (2022) - PAPPA, ELENI; KAKRIDONIS, FOTIOS; TRANTOS, IOANNIS A.; KATSOULIS, PAVLOS; CHATZIKOMNINOS, IOANNIS; ANASTASOPOULOS, JOHN
No abstract available